Search for f J (2220) in radiative J/ψ decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review letters, 2010)
We present a search for fJ(2220) production in radiative J/ψ→γfJ(2220) decays using 460 fb−1 of data collected with the BABAR detector at the SLAC PEP-II e+e− collider. The fJ(2220) is searched for in the decays to K+K− and K0SK0S. No evidence of this resonance is observed, and 90% confidence level upper limits on the product of the branching fractions for J/ψ→γfJ(2220) and fJ(2220)→K+K−(K0SK0S) as a function of spin and helicity are set at the level of 10−5, below the central values reported by the Mark III experiment.
Im Titel ist die Zahl "J" nach "f" tiefgestellt
Im Titel ist "function" als mathematisches Zeichen dargestellt
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, U. Uwer, T. Hartmann, T. Leddig, H. Schröder, R. Waldi [und viele weitere]
Gesehen am 23.08.2023